2004
DOI: 10.1111/j.1440-1754.2004.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary pancreatitis in a family of Aboriginal descent

Abstract: Hereditary pancreatitis is an autosomal dominant condition characterized by recurrent episodes of acute pancreatitis, usually starting in childhood. We present a family who was ascertained when an 11-year-old girl presented with an episode of acute pancreatitis. Her father and other family members had also had recurrent bouts of acute pancreatitis. Genetic testing revealed a pathogenic mutation in the cationic trypsinogen gene in the proband, her father and her paternal grandmother. As far as we are aware, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…They have been frequently reported from Europe, North America, and Asia [Nishimori et al, 1999] and R122H was also recently found in a family of Aboriginal descent in Australia [McGaughran et al, 2004]. Neither mutation was detected in two hereditary pancreatitis families from Brazil [Bernardino et al, 2003] and no hereditary pancreatitis cases have been reported from Africa.…”
Section: N29i and Enhanced Trypsinogen Autoactivationmentioning
confidence: 91%
“…They have been frequently reported from Europe, North America, and Asia [Nishimori et al, 1999] and R122H was also recently found in a family of Aboriginal descent in Australia [McGaughran et al, 2004]. Neither mutation was detected in two hereditary pancreatitis families from Brazil [Bernardino et al, 2003] and no hereditary pancreatitis cases have been reported from Africa.…”
Section: N29i and Enhanced Trypsinogen Autoactivationmentioning
confidence: 91%
“…They have been frequently reported from Europe, North America and Asia [56] and R122H was also recently found in a family of Aboriginal descent in Australia [57]. Neither mutation was detected in two hereditary pancreatitis families from Brazil [58] and no hereditary pancreatitis cases have been reported from Africa.…”
Section: Other Genes Associated To Chronic Pancreatitismentioning
confidence: 95%
“…Further, 12% of adults admitted to hospital because of chronic pancreatitis were Indigenous people, some of whom may have had undiagnosed hereditary pancreatitis. A 2004 case report 25 described an Indigenous family with several members who had hereditary pancreatitis; in our reports on total pancreatectomy and islet auto‐transplantation (TP‐IAT), most patients with hereditary pancreatitis were also Indigenous people 5,16 . The prevalence of exocrine pancreas disorders is generally higher in indigenous than European origin populations 24 .…”
Section: Discussionmentioning
confidence: 83%